Wide-bandgap, low-bandgap, and tandem perovskite solar cells - Song, Zhaoning; Chen, Cong; Li, Chongwen; Awni, Rasha A; Zhao, Dewei; Yan, Yanfa (Semiconductor science and technology, 2019)
Organic-inorganic metal halide perovskite single-junction solar cells have attracted great attention in the past few years due to a high record power conversion efficiency (PCE) of 23.7% and low-cost fabrication processes. Beyond single-junction devices, low-temperature solution processability, and bandgap tunability make the metal halide perovskites ideal candidates for fabricating tandem solar cells. Tandem solar cells combining a wide-bandgap perovskite top cell and a low-bandgap bottom cell based on mixed tin (Sn)-lead (Pb) perovskite or a dissimilar material such as silicon (Si) or copper indium gallium selenide (CIGS) offer an extraordinary opportunity to achieve PCEs higher than Shockley-Queisser (SQ) radiative efficiency limits (∼33%) for single-junction cells. In this review, we will summarize recent research progress on the fabrication of wide- (1.7 to 1.9 eV) and low-bandgap (1.1 to 1.3 eV) perovskite single-junction cells and their applications in tandem cells. Key challenges and issues in wide- and low-bandgap single-junction cells will be discussed. We will survey current state-of-the-art perovskite tandem cells and discuss the limitations and challenges for perovskite tandem cells. Lastly, we conclude with an outlook for the future development of perovskite tandem solar cells.